Assessing the Utility of an Online Adaptive Tool in a Large Undergraduate Psychology Program : Final Report. - Dry, Matthew; Due, Clemence; Chur-Hansen, Anna; Burns, Nicholas (Office for Learning and Teaching, 2017)
In recent years there has been growing interest in the use of e-learning tools that are able to adapt to suit the ability levels, needs, or preferences of individual learners. However, to date there is little robust empirical evidence available that directly assesses the utility of adaptive e-learning tools in regards to academic outcomes. In this project we aim to test the utility of an online adaptive e-learning tool within the context of a large (N=700) undergraduate Psychology course. The authors tested the impact of the tool on academic outcomes, while controlling for a range of psychological and demographic variables that are known to influence academic success. The project has the potential to make an important contribution to learning and teaching at a tertiary level by providing empirical evidence that will address a gap in our current knowledge of the effects of e-learning on academic outcomes.